F03 Huntington Quality Of Life Interview (HQOLI): a new huntington's disease-specific quality of life instrument. (16th November 2010) - Clay, E; Dorey, J; Tedroff, J; Verny, C; Toumi, M; Abélléa, S
Abstract : Background: Health-related QoL (HRQoL) instruments are critical for assessing disease burden. Generic tools allow comparison between diseases but are insensitive and do not discriminate between disease severities. Specific tools tend to be more sensitive and discriminative. No specific tool is available to assess HRQoL in patients with Huntington's disease (HD). In the context of the large and comprehensive European study on HD burden (Euro-HDB), a specific HRQoL tool was needed. Aims: To assess patient HRQoL, and to capture changes related to intervention in early and intermediate stages of HD. Methods: After a semi-structured interview with patients, caregivers and HD specialists, we ran a patient focus group. A self-reported questionnaire was then devised in French (42 items, 11 dimensions) and translated into English, Spanish, German, Italian, Swedish, Portuguese and Polish. In France, 178 patients were recruited to answer the questionnaire—face validity was tested according to item response rate; internal and external validity were examined using a variety of methods. Results: Face validity and internal validity were acceptable. A high correlation of several items within the same dimension suggests item number can be reduced. As expected, there was a significant ceiling effect, suggesting high sensitivity at early and intermediate HD stages but low sensitivity later on. External validity supports scale robustness. HRQoL is worst in the most severe patients; depression dramatically affects HRQoL. Patient and caregiver HRQoL do not overlap completely. Voluntary motor symptoms contribute significantly to HRQoL, but chorea does not. Conclusions: These data support the validity of the HQOLI in patients with HD. Sensitivity analyses, test–retest reliability and cross-cultural validation will be performed/are underway. The ceiling effect limits the use of the HQOLI in late stages of HD.